Analisis Perlindungan Hukum Bagi Pihak Yang Memiliki Hak Atas Tanah - Gabriel Nugeraha Silalahi; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2024)
This research aims to analyse the form of legal protection for parties who own land rights and analyse the legal certainty of land rights certificate holders through a case study of Banjarbaru District Court Decision Number 62/Pdt.G/2022/PN Bjb. This research uses normative juridical research by analysing secondary data in the form of primary, secondary, and tertiary legal materials. The results showed that the court decision provided legal protection for Sudjar Wadi as a party with land rights through recognition of the validity of the land sale and purchase transaction, the right to appear before the Land Deed Official (PPAT), to transfer the name of the land certificate, and to take care of the lost certificate. This decision also emphasises the importance of legal certainty in protecting the rights of land certificate holders by ensuring Sudjar Wadi has legal rights to the disputed land. Law enforcement in this case achieved the goals of legal certainty, social benefit, and justice by determining the defendant to bear the costs of the case, providing incentives for effective law enforcement, and is expected to increase public confidence in judicial institutions and compliance with the rule of law.